Ewaluacje konstruktywistyczne. Implikacje dla wczesnej edukacji - Henryk Mizerek (Problemy Wczesnej Edukacji)
The aim of this paper is to analyze the possibilities of using evaluation models – developed within the constructivist paradigm – in early education. The author’s field of interest included responsive evaluation, dialogic evaluation, deliberative democratic evaluation, participatory evaluation, empowerment evaluation and stakeholder-based evaluation. Responsive and dialogical evaluation have been found to be particularly useful in early education. The scope of in-depth analyzes is aimed to present the specificity of responsive dialogical evaluations compared to other constructivist models and their distinctiveness from neoliberal evaluations and those subordinated to the gold standard ideology. The content of the second part of the paper is devoted to analyze the problems of designing, planning and conducting programs implemented in early education.